Coordination chemistry of ligands: Insights into the design of amyloid beta/tau-PET imaging probes and nanoparticles-based therapies for Alzheimer’s disease - Tamil Selvan, Subramanian; Ravichandar, Roopa; Kanta Ghosh, Krishna; Mohan, Anand; Mahalakshmi, Pachaiyappan; Gulyás, Balázs; Padmanabhan, Parasuraman (Coordination chemistry reviews, 2021)
[Display omitted] •Clinically approved Aβ-PET tracers for different neurodegenerative diseases.•Superior cognitive performance of Florbetapir and FDG in distinguishing AD from MCI.•Aβ tracers with low topographical distribution, association with clinical severity.•Studies on the association of subcortical striatal Aβ with faster cognitive decline.•Potential tau-PET probes (e.g., [18F]-MK-6240, [18F]-AV-1451) for AD and non-AD.•Organic therapeutic nanoparticles with natural antioxidants (e.g., green tea).•Inorganic NPs (e.g., Au, CeO2) for inhibition of amyloid and tau aggregation. The diagnosis and therapy of neurodegenerative diseases are highly indispensable. In particular, the definitive clinical diagnosis and therapy of Alzheimer’s disease (AD) remains a challenge. Despite the use of amyloid beta (Aβ) positron emission tomography (PET) gold standard [11C]-PiB, other approved benzothiazole ([18F]-flutemetamol) and stilbene derivative ([18F]-florbetaben and [18F]-florbetapir) based probes have been extensively studied and advocated as potential early Aβ PET radioligands for AD. Recent years have witnessed a burgeoning research activity in the development of radiotracers for tau neurofibrillary tangles (NFTs) binding using PET imaging, while monitoring the progression of disease. Notably, several tau PET ligands (e.g. [18F]-THK5351, [18F]-MK-6240, and [18F]-AV-1451, [18F]-RO-6958948, [18F]-JNJ-64326067, [18F]-PI-2620) showed high affinity and selective binding to tau pathology. Although early detection and progression of AD have been studied extensively using PET imaging, therapeutic approaches to the disease are scarce. Recently, nanoparticles (NPs) based therapeutic approaches have emerged. Coordination of ligands to the surface of organic NPs (e.g., flavonoids: green tea polyphenol- EGCG, curcumin), and inorganic NPs (e.g. Au, ZnO, CeO2) have been explored to decrease/inhibit the amyloid aggregation and tau hyperphosphorylation. This review focuses on (i) the importance of coordination chemistry of ligands in the design of PET imaging probes with specific binding affinities to Aβ and tau NFTs in AD, and (ii) the role of surface ligands and their coordination to NPs and functional molecules for the rational design of novel anti-AD reagents for therapeutic interventions.